The Impact of Board Characteristics on Disclosure Quality before and After Adopting IASs: An Empirical Study on Saudi Joint Stock Companies - Alsulamy, Kholoud Awadallah; Basheikh, Abdullatif Mohamed; Boshnak, Helmi A. (International Journal of Economics and Financial Issues, 2025)
This study examines the impact of directors’ characteristics on disclosure quality in Saudi joint stock companies before and after the adoption of international accounting standards. The study employs an inductive approach to analyze quantitative data. The study sample comprises 98 non-financial companies listed on the Saudi Stock Exchange (Tadawul) over two periods: 2011-2016 representing the pre-adoption stage of international standards, and 2017-2022 representing the post-adoption stage. The theoretical framework is grounded in agency, stewardship, and resource dependence theories to explain the impact of directors’ characteristics on disclosure quality, and the relationship between variables is analyzed using multiple regression analysis. The results show that before the adoption of international standards, board size, independence, and role duality had a positive impact on disclosure quality, while board meeting frequency had no effect. In contrast, after the adoption of such standards, board size and role duality no longer had any effect, while the impact of board member independence became negative, and board meeting frequency remained insignificant. This study contributes to the accounting and governance literature by presenting evidence from the Saudi environment on the effect of board characteristics on disclosure quality before and after the adoption of international accounting standards.